Exploring the professional identity and agency of student teachers in multilingual classrooms. (4th March 2022) - Foley, Yvonne; Anderson, Charles; Hancock, Jonathan; Conteh, Jean
ABSTRACT: While there is now a considerable body of work on teacher identity in the area of language education, much less attention has been given to the question of the extent to which student teachers are enabled to construct identities that are consonant with the opportunities and challenges of current multilingual classrooms. Drawing on a recent large-scale research and development project, this article explores how the student teachers in our study: understood their responsibilities towards pupils for whom English is an Additional Language; perceived their development needs, preparedness and confidence to support EAL pupils; the constraints they encountered; and the opportunities that they utilized to be and act responsively within multilingual classrooms. Findings are contextualized within the policy framework concerning language and the variegated landscape of Initial Teacher Education (ITE) in England; and framed against apposite perspectives on identity and agency, with a central place being given to socio-cultural theories of identity formation which focus on discourse and practice. Building on the findings, the Discussion points up some of the elements that need to be in place if student teachers are to develop a professional identity that is truly inclusive and responsive to linguistic and cultural difference .